Perbandingan Efektivitas Handrub Softa-ManÂ® Dan Formula Handrub Moewardi Terhadap Angka Kuman Di RSUD Dr. Moewardi - Jeffrey F .L, Henrikus; Saptawati, Leli; Marwoto, . (Nexus Biomedika, 2013)
Background: Nosocomial infections are important clinical problem, indicated by many cases on the incidence of nosocomial infections. To overcome this incident, a lot of researchers have conducted variety of ways, one of them is hand hygiene. Two different kinds of hand hygiene alcohol-based products were used in this study, handrub Softa-manÂ® and Moewardiâs handrub formula. The effectiveness of both handrub in reducing the number of bacteria was compared on health-care workers. Methods: This study was a quasi-experimental study. The study was conducted at hospital wards in Dr. Moewardi Hospital. Respondents were taken by consecutive sampling. There were two groups in this study, the group that received handrub Softa-manÂ® and the group that received Moewardiâs handrub formula. Each group was observed for the effectiveness in reducing the number of bacteria. The data that had been collected then were analyzed using the Mann-Whitney test and followed by Wilcoxon test. Results: The results of this study showed that both groups managed to reduce the number of bacteria. Wilcoxon test result showed a difference in the number of bacteria before and after hand washing where the number of bacteria after hand washing was fewer than before hand washing. The result of Mann-Whitney test showed that there was no statistical difference in the decreased number of bacteria when both handrub were compared. Conclusions: There was no significant difference in the decreased number of bacteria between the Softa-manÂ® handrub and Moewardiâs handrub formula usage. Keywords: Handrubâs effectiveness, Alcohol-based handrub, Softa-manÂ®, Moewardiâs formula, Number of bacteria.